The wisdom of the bullfrog : leadership made simple (but not easy) - McRaven, William H. (William Harry), 1955- (Grand Central Publishing, 2023)
"The title "Bullfrog" is given to the Navy SEAL who has served the longest on active duty. Admiral McRaven became the Bullfrog in 2011 having dealt with every conceivable leadership challenge. The Wisdom of the Bullfrog draws on these and countless other experiences from his incredible life. Each chapter provides a Make Your Bed-like parable about the specific leadership traits required to be at the top of your game, including: Who dares wins, Run to the sound of the guns, no plan survives first contact with the enemy. The Wisdom of the Bullfrog is Admiral McRaven's treatise on the leadership qualities that separate the good from the truly great."--Page [2] of cover.